Evaluation of dental implants failure rate in medically compromised patients: A randomized case control study (Journal of Pharmaceutical Negative Results, 2022)
Aim: The present research was done to evaluate dental implant failure in medically compromised patients compared to control group.Materials and Method: This randomized control study comprised of 50 medically compromised patients of both genders who underwent dental implants 7 years ago (Group I). Equal number of healthy subjects was taken as control (Group II). Amount of bone loss around the implant over 1mm of bone loss in the first year and over 0.3 mm bone loss every subsequent year were considered as failures.Results: The most commonly seen medically compromised patients were diabetes (20) with 24 dental implants followed by Hypothyroidism (12) with 12 implants, osteoporosis (8) with 15 dental implants, organ transplant (7) with 8 dental implants and CVD (3) with 3 dental implants. There was statistically significant difference (p< 0.05). The implant failure was 15 (30%) in group I, and 3 (6%) in group II. At first year, in group I, mean bone loss around implant was 1.18 mm and 0.4 mm in group II. Up to 5 years, in group I, mean bone loss around implant was 2.8 mm and 1.3 mm in group II.Conclusion: Among medically compromised conditions, higher failure rate was found in diabetes.